Synergistic deformation mechanisms in Cu–Fe layered materials: a strain gradient plasticity finite element analysis - Ran, Hao (2024)
The hetero-zone boundary affected region (HBAR), with a high strain gradient, plays a crucial role in the synergistic deformation of layered materials. Our previous experimental study demonstrated that a decreasing interfacial spacing leads to a higher fraction of HBAR and an enhanced combination of strength and ductility. In this work, a conventional mechanism-based strain gradient (CMSG) plasticity model is adopted to simulate the tensile behavior of Cu–Fe layered materials with three different interfacial spacings. The simulation results indicated that strain/stress partitioning and strain banding are the main factors for the synergistic deformation behavior. Strain bands are more likely to be activated in the Cu–Fe layered materials with smaller interfacial spacing. In addition, the formation of HBAR near the layer boundary can be observed, consistent with the previous experiments. During deformation, the HBAR induces back stress and forward stress to strengthen the Cu layer and weaken the Fe layer, respectively. The simulation results indicate the stress transfer between the Cu and Fe layers, which benefits the strain hardening and enhances synergistic deformation. This study provides a valuable insight into the strength-ductility synergy of layered materials. It demonstrates that increasing the HBAR fraction is a viable approach to enhance the mechanical properties of hetero-structured materials.